1996
DOI: 10.2807/esm.01.04.00160-en
|View full text |Cite
|
Sign up to set email alerts
|

Mumps epidemic in Portugal despite high vaccine coverage - preliminary report

Abstract: A measles, mumps, and rubella (MMR) trivalent vaccine was added to Portugal's National Immunisation Programme (NIP) in 1987. All vaccines are given at health centres, free of charge, but an epidemic of mumps began in 1995, firstly in northern Portugal and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Substantial numbers of cases occurred in children of 1 to 4 years of age in kindergartens, schools, and other child care facilities and at least 40-60% of these had a history of mumps vaccination [Dias et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial numbers of cases occurred in children of 1 to 4 years of age in kindergartens, schools, and other child care facilities and at least 40-60% of these had a history of mumps vaccination [Dias et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…However, sporadic mumps outbreaks are reported even in countries which are known to have an excellent record of vaccine coverage [Briss et al, 1994;Kü nkel et al, 1994;Ströhle et al, 1996;Dias et al, 1996]. In order to distinguish whether the recent outbreak in Portugal was caused by endemic European strains or by imported genotypes, clinical specimens derived from patients were characterised by RT-PCR, nested PCR, and nucleotide sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, where until recently the Rubini strain was commonly used, modelled sero-conversion rates were very low -approximately 60 % [12]. The Rubini strain has been shown not to offer good protection against the disease [25,26], and the use of this strain in the MMR vaccine, as well as the poor vaccine coverage, may have contributed to the low mumps virus antibody positivity observed.…”
Section: Discussionmentioning
confidence: 99%
“…In Portugal, MMR coverage of children aged 12-23 months has been >90% since 1991; despite this, a large mumps epidemic occurred in 1995-96 with the highest incidence among children aged 1-4 years. A plot of the number of cases according to their probable month and year of vaccination showed that there was a large increase in mumps incidence among children vaccinated after October 1992, which corresponded to the date when Portugal began to use the Rubini strain of mumps vaccine exclusively (63).…”
Section: Immunogenicity Efficacy and Safetymentioning
confidence: 99%
“…The number of reported mumps cases decreased from 2197 in 1987 to 627 in 1993. Subsequently, the country experienced a large epidemic, with 1841 mumps cases in 1995 and 7620 cases in the first 8 months of 1996 (63). Epidemiological investigations suggest the outbreak may have been related to exclusive use of Rubini strain vaccine since October 1992.…”
Section: European Regionmentioning
confidence: 99%